Complete mitogenome and phylogenetic analysis of two species (Mareca penelope and Mareca falcate) - Seon-Mi Lee; Jin Young Park; Wee-Haeng Hur; Hyung-Kyu Nam (Mitochondrial DNA. Part B. Resources, 2021)
We determined the complete mitogenomes of two wigeons, Mareca penelope (16,603 bp) and Mareca falcata (16,597 bp) of the family Anatidae using Illumina next-generation sequencing to better understand phylogenetic relationships. Both species consisted of 37 genes (13 protein-coding genes), two ribosomal RNAs, 22 transfer RNAs, and one control region. A + T content (M. penelope 51.25%, M. falcata 51.2%) was slightly higher than G + C content (M. penelope 48.75%, M. falcata 48.8%). Phylogenetic analysis based on 13 concatenated PCG sequences indicated that M. penelope and M. falcata belong to the Mareca genus, with high bootstrap values.